Small RNAs encoded by human endogenous retrovirus K overexpressed in PBMCs may contribute to the diagnosis and evaluation of systemic lupus erythematosus as novel biomarkers. Issue 9 (11th November 2021) - Liu, Xinyi; Ding, Yanjun; Zheng, Xiaoqiu; Huang, He; Shi, Liyu; Yang, Xiaolan; Wei, Jing; Li, Yang; Kao, Wenping; Zhang, Fengmin; Qian, Jun
Abstract: This study aimed to identify the genes and small RNAs (sRNAs) expressed by the human endogenous retrovirus K (HERV-K) HML2 and their associations with the immune process of systemic lupus erythematosus (SLE). RNA-Seq data including 99 SLE patients and 18 controls (GSE72420) was obtained from the Gene Expression Omnibus. Differentially expressed genes (DEGs) as well as HML2-DEGs between SLE patients and normal controls were identified. Five HML2-DEGs involved in immune-regulating function were identified using weighted gene co-expression network analysis. The associations between these genes and the proportions of immune cells were determined by CIBERSORT. Ten candidate HML2-encoded sRNAs were identified based on specific criteria, and three of them were further validated in SLE patients by qRT-PCR. The diagnostic values of these three sRNAs were evaluated in SLE and lupus nephritis (LN). This study suggested that HML2 genes and their encoded sRNAs might be involved in the immune regulation and progress of SLE. These potential sRNAs might function as regulatory molecules and diagnostic biomarkers of SLE and LN.